Determinant Development of Airport Service Quality at Terminal 2 Soekarno Hatta - Muhammad Faisal; Juliater Simarmata; Primadi Candra Susanto (Dinasti Publisher, 2024)
The article on determinants of the development of airport service quality at terminal 2 Soekarno Hatta is a scientific literature article within the scope of human resource management science. The purpose of this writing is to build a hypothesis regarding the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and the journal Sinta. The results of this article are: 1) The airport security system influences the development of airport service quality; 2) Airport infrastructure influences the development of airport service quality; and 3) Customer values influence the development of airport service quality.